English literacy among maritime graduates: a study at STIP Jakarta - Marudut Bernadtua Simanjuntak; Retno Sawitri Wulandari; Larsen Barasa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research investigates English literacy proficiency among graduates of Maritime Institute Jakarta (STIP Jakarta), focusing on deck officers, engine officers, and shipping professionals. The study aims to assess proficiency levels, identify factors influencing English acquisition, and evaluate alignment with International Maritime Organisation (IMO) Standards of Training, Certification, and Watchkeeping (STCW).The research employs qualitative interviews with 70 alumni to explore proficiency levels, instructional quality, exposure, and personal motivation. STIP Jakarta's curriculum is also analyzed for its alignment with IMO-STCW standards, particularly in communication skills and technical terminology. The findings reveal varied proficiency levels across skills, with implications for effective communication, compliance with regulations, and career advancement in the maritime industry.The study highlights the importance of targeted interventions to address proficiency gaps and recommends collaborative efforts to enhance English literacy education in maritime institutions. This is crucial for fostering safety and professionalism in the global maritime industry.